Effect of CYP4F2, VKORC1, and CYP2C9 in Influencing Coumarin Dose: A Single‐Patient Data Meta‐Analysis in More Than 15, 000 Individuals. Issue 6 (17th February 2019) - Danese, Elisa; Raimondi, Sara; Montagnana, Martina; Tagetti, Angela; Langaee, Taimour; Borgiani, Paola; Ciccacci, Cinzia; Carcas, Antonio J.; Borobia, Alberto M.; Tong, Hoi Y.; Dávila‐Fajardo, Cristina; Rodrigues Botton, Mariana; et al.
Abstract : The cytochrome P450 ( CYP ) 4F2 gene is known to influence mean coumarin dose. The aim of the present study was to undertake a meta‐analysis at the individual patients level to capture the possible effect of ethnicity, gene—gene interaction, or other drugs on the association and to verify if inclusion of CYP4F2*3 variant into dosing algorithms improves the prediction of mean coumarin dose. We asked the authors of our previous meta‐analysis (30 articles) and of 38 new articles retrieved by a systematic review to send us individual patients' data. The final collection consists of 15, 754 patients split into a derivation and validation cohort. The CYP4F2*3 polymorphism was consistently associated with an increase in mean coumarin dose (+9% (95% confidence interval (CI) 7–10%), with a higher effect in women, in patients taking acenocoumarol, and in white patients. The inclusion of the CYP4F2*3 in dosing algorithms slightly improved the prediction of stable coumarin dose. New pharmacogenetic equations potentially useful for clinical practice were derived.